Actions and attitudes on the immunized patients against SARS-CoV-2 - De Lucas Ramos, Pilar; García Botella, Alejandra; García Lledó, Alberto; Gómez Pavón, Francisco Javier; González del Castillo, Juan; Hernández Sampelayo, Teresa; Martín Delgado, Mari Cruz; Martín Sánchez, Francisco Javier; Martínez Sellés, Manuel; Molero García, José María; Moreno Guillén, Santiago; Rodríguez Artalejo, Fernando; et al. (My University, 2021)
The access to COVID vaccines by millions of human beings and their high level of protection against the disease, both in its mild and severe forms, together with a plausible decrease in the transmission of the infection from vaccinated patients, has prompted a series of questions from the members of the College of Physicians of Madrid (ICOMEM) and the society. The ICOMEM Scientific Committee on this subject has tried to an swer these questions after discussion and consensus among its members. The main answers can be summarized as follows: The occurrence of new SARS-CoV-2 infections in both vaccinated and previously infected patients is very low, in the observation time we already have. When breakthrough infec tions do occur, they are usually asymptomatic or mild and, purportedly, should have a lower capacity for transmission to other persons. Vaccinated subjects who have contact with a SARS CoV-2 infected patient can avoid quarantine as long as they are asymptomatic, although this decision depends on variables such as age, occupation, circulating variants, degree of contact and time since vaccination. In countries with a high proportion of the population vaccinated, it is already suggested that ful ly vaccinated persons could avoid the use of masks and social distancing in most circumstances. Systematic use of diagnostic tests to assess the immune response or the degree of protection against reinfection af ter natural infection or vaccination is discouraged, since their practical consequences are not known at this time. The exist ing information precludes any precision regarding a possible need for future revaccination. This Committee considers that when mass vaccination of health care workers and the general population is achieved, SARS-CoV-2 screening tests could be avoided at least in out patient care and in the case of exploratory procedures that do not require hospitalization. Keywords: COVID-19, viral variants, SARS-CoV2, vaccine escape, gap COVID-19, use of masks, COVID-19 screening, vaccines, follow-up of immunized persons.